Application of Statistical and Modeling Methods in the Semantic Analysis of Linguistic Units (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article discusses the use of statistical and modeling methods in the semantic analysis of linguistic units in the Uzbek language. Modern linguistics increasingly applies quantitative and computational approaches to analyze word meanings, semantic relations, and contextual dependencies. Statistical tools allow for identifying the frequency and correlation of linguistic features, while modeling techniques help visualize and predict semantic networks. The study emphasizes how combining linguistic theory with statistical modeling can enhance the objectivity and accuracy of semantic analysis and support the development of computational linguistics and digital lexicography.